2021
DOI: 10.1038/s41467-021-26413-6
|View full text |Cite
|
Sign up to set email alerts
|

Arginine methylation and ubiquitylation crosstalk controls DNA end-resection and homologous recombination repair

Abstract: Cross-talk between distinct protein post-translational modifications is critical for an effective DNA damage response. Arginine methylation plays an important role in maintaining genome stability, but how this modification integrates with other enzymatic activities is largely unknown. Here, we identify the deubiquitylating enzyme USP11 as a previously uncharacterised PRMT1 substrate, and demonstrate that the methylation of USP11 promotes DNA end-resection and the repair of DNA double strand breaks (DSB) by hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…We next addressed how PRMT1 regulates the protein level of C/EBPβ. PRMT1 has been proven to be associated with protein stability and ubiquitination in multiple cells ( 28 , 29 , 30 , 31 ). To pinpoint whether PRMT1 affects the stability of C/EBPβ, 3T3-L1 cells transfected with siCtrl or siPRMT1 were harvested after the translational inhibitor cycloheximide pretreatment for 0, 2, 4, 6, and 8 h and then C/EBPβ protein expression was analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next addressed how PRMT1 regulates the protein level of C/EBPβ. PRMT1 has been proven to be associated with protein stability and ubiquitination in multiple cells ( 28 , 29 , 30 , 31 ). To pinpoint whether PRMT1 affects the stability of C/EBPβ, 3T3-L1 cells transfected with siCtrl or siPRMT1 were harvested after the translational inhibitor cycloheximide pretreatment for 0, 2, 4, 6, and 8 h and then C/EBPβ protein expression was analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to the effect on methylation, PRMT1 positively regulates the phosphorylation of C/EBPβ. Previous studies have suggested that PRMT1 participates in regulating protein stability ( 28 , 29 , 30 , 31 ). PRMT1 interacts not only with ribosome and proteasome constituents but also with deubiquitinases, such as USP7, that promotes protein stability ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between different posttranslational modifications are critical for the DNA damage response. Arginine methylation has an essential role in maintaining genome stability, and arginine methylation and ubiquitination crosstalk control DNA end resection and HR repair (68). Mass spectrometry analysis of PRMT1-interacting proteins revealed that ubiquitin specific peptidase 11 (USP11) has a key role in the early stage of DSB repair by regulating the activity of the PRMT1-MRE11 pathway.…”
Section: Methylation Of Nonhistonesmentioning
confidence: 99%
“…USP11 is a substrate of PRMT1 and methylation of USP11 promotes DNA end resection and DSB repair of DNA through HR. PRMT1 is also a ubiquitinated protein that acts as a target of de-ubiquitination to regulate the binding and methylation of PRMT1 to MRE11 (68). RNA splicing is critical for regulating tumour phenotypes (69,70).…”
Section: Methylation Of Nonhistonesmentioning
confidence: 99%
“…Meanwhile, the BRCA1-BARD1 complex promotes DNA end resection by antagonizing the 53BP1-RIF1 complex in a cell cycle-dependent manner 13 . To date, a series of post-translational modifications (PTMs), including phosphorylation and ubiquitylation, have been reported to regulate DNA end resection 14,15,16 . For example, phosphorylation of CtIP is required for the MRN endonuclease activity that initiates DNA end resection 17 .…”
Section: Introductionmentioning
confidence: 99%